Mindfulness in Salah Prayer: Understanding Khusyu’ from A Psychological Term Approach - Al-Razi, Muhammad Fakhruddin; Mukti, Sri (Proceeding International Conference on Religion, Science and Education, 2025)
Khusyu' is one of the factors that determine the quality of a Muslim's prayer. However, in scientific studies, the concept of khusyu' has not received significant attention among researchers. Given that khusyu' is a mental phenomenon, the psychological approach is important in studying this aspect. This study aims to examine khusyu' through a psychological approach by reviewing relevant literature. One of the psychological concepts considered to be in line with khusyu' is mindfulness. Through the literature review, this study found an alignment between khusyu' and mindfulness, where khusyu' can be understood as a form of mindfulness in prayer. The main characteristics of khusyu' include a full presence in prayer, inner calmness, and a centered focus on worship without being distracted by outside thoughts. In addition, khusyu' involves deep contemplation of the meaning of the movements and recitations in prayer. Thus, this study concludes that khusyu' can be conceptualized as mindfulness in the context of prayer, which is characterized by deep mental and emotional presence and spiritual meaning to each component of worship. The findings are expected to enrich academic discussions on khusyu' and open up further research opportunities in the field of psychology of religion, particularly in relation to Muslim worship practices.